From Waste Management to Circular Resource Management - Maters, Erna; Luttik, Joke (Journal of Sustainability Perspectives, 2021)
The circular economy is a topic researched by Wageningen University & Research (WUR). In addition to better waste management WUR strives to reduce the use of resources in its operational management. Recently WUR’s executive board ratified a Circular economy policy, vision & strategy 2019-2030. Aim is to achieve a 50% reduction in the use of resources in 2030, compared to 2014. This ambition follows the circular economy policy launched by the Dutch government.By buying fewer products, making smarter use of products, extending their lifespan and re-using products within WUR or elsewhere, WUR will reduce the number of resources used, as well as the amount of waste that is incinerated or recycled. In order to follow the progress of WUR’s circular economy policy WUR will also monitor the usage of resources, in addition to the current waste monitoring. Strategies proposed are to extend the use of products, to recycle products for new purposes, extending the lifespan of new products and to close the circle for new products fully. The success of WUR’s circular economy policy depends on acceptance and support by, and behaviour of students and employees whose expertise WUR will furthermore use where possible. WUR will also cooperate where possible with other organisations and companies.